Supply Flexibility in the Shale Patch: Evidence from North Dakota - Hilde C. Bjørnland; Frode Martin Nordvik; Maximilian Rohrer (Norges Bank, 2017)
We question whether supply flexibility in oil production depends on the type of extraction technology. In particular, we ask if shale oil producers respond to price incentives when producing oil or completing new wells. Constructing a novel well-level monthly production data set covering more than 16,000 crude oil wells in North Dakota, we find large differences in responses depending on which technology is used: While output from conventional wells appear non-responsive to price fluctuations in the short-term, we find supply elasticity to be positive and in the range of 0.3-0.9 for shale oil wells, depending on wells and firms characteristics. Furthermore, shale oil firms respond strongly to prices when deciding when to put new oil wells on stream, while conventional oil firms do not. Overall, our results suggest that firms using shale oil technology are more flexible than those using conventional production techniques. We interpret the supply pattern of shale oil wells to be consistent with the Hotelling theory of optimal extraction.
hdl:11250/2495581
Keywords: C33; L71; Q31; Q40; 330; US oil shale boom; Hotelling's theory; oil extraction; crude oil prices